Odpowiedzi

  • Użytkownik Zadane
2010-01-18T17:30:06+01:00
A). 1/4abb*(-2a)
1/4abb*(-2a)= -1/2a²b²
b). 3x(do kwadratu) y *(-1/6xy)
3x²y *(-1/6xy)= -1/2 x³y²
c). -3(-x)(-x)(-y)
-3(-x)(-x)(-y)= -3x²y
d). 0,2tsts(do kwadratu)*(-15)( Wziąłem do kwadratu tylko ostatnie s)
0,2tsts²*(-15)= -3t²s³
4 3 4
Najlepsza Odpowiedź!
2010-01-18T17:57:00+01:00
A). 1/4abb*(-2a)
¼ ab² * (-2a) = - ½ a²b²
b). 3x(do kwadratu) y *(-1/6xy)
3x²y * (-⅙xy) = - ½ x³y²
c). -3(-x)(-x)(-y) = 3x * (-x) * (-y) = - 3x² * (-y) = 3x²y
d). 0,2tsts(do kwadratu)*(-15)
0,2tsts² * (-15) = - 3t²s³